2006
DOI: 10.1258/026835506775971199
|View full text |Cite
|
Sign up to set email alerts
|

Heat dissipation during endovenous laser treatment of varicose veins – is there a risk of nerve injury?

Abstract: Objective: Endovenous laser therapy (EVLT) is a new minimally invasive treatment for varicose veins employing laser ablation of the long saphenous vein (LSV) under tumescent local anaesthesia. Concerns about thermal injury to perivenous nerves (tibial, peroneal, sural) have prevented its use for saphenopopliteal/short saphenous incompetence. This study assesses heat dissipation around the LSV during EVLT. Methods: In 12 consenting patients undergoing EVLT (Local research ethics committee approved), thermocoup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…In all 42 extremities, the etiology was primary and the pathophysiology was related with reflux. Superficial venous insufficiency was found in EVLA treatment of the small saphenous vein may be related with a higher rate of nerve injury because of adjacency to the sural nerve (18). In our study, varying degrees of tenderness and ecchymosis were observed in 34 (81%) extremities at the one-week follow-up vizit.…”
Section: A B Csupporting
confidence: 45%
“…In all 42 extremities, the etiology was primary and the pathophysiology was related with reflux. Superficial venous insufficiency was found in EVLA treatment of the small saphenous vein may be related with a higher rate of nerve injury because of adjacency to the sural nerve (18). In our study, varying degrees of tenderness and ecchymosis were observed in 34 (81%) extremities at the one-week follow-up vizit.…”
Section: A B Csupporting
confidence: 45%
“…Distance X was used to create the upper lateral landmarks (13,14). Distance Y was used to create the upper medial landmarks (15,16). Distance X ϭ one-third of the distance between landmark 1 and 3.…”
Section: General Assessmentsmentioning
confidence: 99%
“…Local tumescent anesthesia is known to protect surrounding tissue from high coagulation temperatures. 16 When the distance between the SSV and SN is Ͻ1 mm, the SN runs immediately next to or partly under the SSV. Insertion of tumescent anesthesia exactly between the SSV and the SN might therefore be difficult, if not impossible.…”
Section: Because the Location Of The Spj Shows No Correlationmentioning
confidence: 99%
“…Published reports confirm that endovenous laser ablation of an incompetent great saphenous vein (GSV) [1][2][3][4][5][6] or small saphenous vein (SSV) 7,8 is safe 9 and can provide outcomes equal to or better than traditional surgical ligation and stripping. [10][11][12][13] Some practitioners advocate ablating the thigh segment of the GSV and treating the remaining visible varicosities with sclerotherapy during subsequent follow-up visits.…”
mentioning
confidence: 99%